3/(log_2 (a)) - 2/(log_4 (a)) = 1/(log_(1/2)(a))
since 4 = 2^2, log_4(a) = 1/2 log_2(a)
since 1/2 = 2^-1, log_(1/2)(a) = -log_2(a)
so, if we let x = log_2(a), we have
3/x - 2/(x/2) = 1/(-x)
3/x - 4/x = -1/x
(4-3)/x = -1/x
1/x = -1/x
Is there a typo somewhere ?
Make sure its just like that, it has to be solvable o.o
math - Prove. 3/(log_2 (a)) - 2/(log_4 (a)) = 1/(log_(1/2)(a))
ICA Honors - 1/log_2(X) + 1/log_3(x) + 1/log_4(x) +1/log_5(x) =log_5(625)
Pre-Calculus - My book doesn't explain how to do these problems.. The examples ...
algebra - solve the logarithm log_2 (x -1)- log_2(5x +1) = -3 I got -3, is this ...
Math - Logarithmic - log_5[log_4(log_3(x))] = 1 log_5 = log with the base of 5 ...
math - find the inverse. f(x)=-2+log_4(x-4)
advanced math - Solve the equation. 2log_2(x-5)+log_2(2)=5
calculus (math) - Simplify exactly log_2 1/16
math - My math teacher wants us to prove that all of our answers are correct. ...
Math - The aperture setting, or f-stop, of a digital camera controls the amount ...